Pencegahan Penyakit Tidak Menular melalui Program PKMD: Strategi Pemeriksaan dan Edukasi Kesehatan Masyarakat - Yuningsih, Aneng; Nasrulllah, Igal Mulki; Yulia, Elsa; Fitriyana, Elsa Destira; Shalehah, Livia Raissa; Nurmila, Zakia; Nurhakim, Azi Farhan; Agustiani, Risna; Rosyidah, Hani; Baihaki, Muhamad Akmal; Agustin, Wisa Putri; Jarnauziah , Faza Aulia (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Abstract Non-Communicable Diseases (NCDs) such as hypertension, diabetes mellitus, and eye disorders are increasingly prevalent in RT 002 RW 005 Sukasukur, Kersanagara Village, Tasikmalaya City, primarily due to unhealthy lifestyles, including poor dietary habits, lack of physical activity, and smoking. The Village Community Health Development Program (PKMD), organized by the Faculty of Health Sciences, Universitas Bakti Tunas Husada, aims to provide health education and health screenings to the community to reduce the incidence of NCDs in the area. The program includes health education on healthy living, the importance of early detection, and routine screenings such as blood pressure, blood sugar, eye exams, and others. A community-based approach was used, combining education with direct health screenings. Pre- and post-test evaluations show a significant increase in community knowledge regarding NCDs and preventive measures. The success of the program is attributed to active community participation and effective collaboration between academics, health professionals, and local government. The PKMD program has proven to be effective in raising awareness about the importance of adopting a healthy lifestyle, with the aim of reducing the prevalence of NCDs and improving the overall quality of life in the community. The program also supports the integration of primary healthcare services to be implemented in Tasikmalaya City.